Haematological studies of some Breeds of cattle in the humid forest zone of Ghana - Obeng, A.M. (1989)
The haematological values of N'Dama, West African Shorthorn (WASH) and N'Dama x Friesians crossbreds were investigated. Records from 31 N'Dama, 20 WASH and 21 N'Dama x Friesians crossbreds were analysed. Analyses results showed no significant effects of age and sex on both haematological and biochemical values. Haematological values of one breed cannot be used as a diagnostic tool for another; neither can the biochemical value of one sex be used for another within the same breed.